EVALUATION OF DIS-LUBTOUT, A NEW COPROCESSED TABLETING EXCIPIENT 3. PHYSICO-CHEMICAL PROPERTIES OF WET GRANULATION ASPIRIN TABLETS LUBRICATED WITH DIS-LUB-TOUT - Shabbeer, FA; Aly, SAS (European Scientific Journal, ESJ, 2014)
Dis-Lub-Tout, a newly co-processed bi-functional tableting excipient was evaluated against magnesium stearate, MS, for its lubricant property and in a model wet granulation ASA tablet system prepared with lactose as tabletted based material. Dis- Lub-Tout increased the flow rate and negatively affected the densification behavior of the tested formulations. It accelerated the disintegration and dissolution rates of the tested tablets which were functions of the concentration of the lubricant in the tested tablets. Thermo-degradation study showed that the decomposition of ASA in tablets lubricated with Dis-Lub-Tout followed the pseudo first order pattern with slower rates which were amenable to Arrhenius treatment. ASA degradation rate constants in tablets stored under humid conditions was faster.